The subsurface Flow and Transport Experimental Laboratory: a new Department of Energy user's facility for intermediate-scale experimentation - Oostrom, M., author; Wietsma, T. W., author; Foster, N. S., author; Colorado State University, publisher (Colorado State University. Libraries, 2004)
Intermediate-scale experiments for flow and transport are important for the physical simulation of subsurface features and conditions encountered in the field at government and private sites. To offer a capability where scientists and engineers are able to conduct such experiments, a new facility has been developed in the Environmental Molecular Sciences Laboratory at the Pacific Northwest National Laboratory. The new facility, called the Subsurface Flow and Transport Experimental Laboratory (SFTEL), offers a variety of columns and flow cells, a new state-of-the-art dual-energy gamma system, a fully automated saturation-pressure apparatus, and extensive analytical equipment for sample processing. The new facility, including qualified staff, is available free of cost for scientists interested in collaboration on conducting high-quality flow and transport experiments, including contaminant remediation. Close linkages exist between the SFTEL and numerical modelers to aid in experimental design and interpretation. In this paper, the new facility is discussed and some examples of recent intermediate-scale experiments are presented.
Hydrology days 2004
AGU hydrology days 2004
24th annual AGU hydrology days was held at Colorado State University on March 10-12, 2004.